Crowd-Based Geodata Production and Platform Capitalism: The Case of OpenStreetMap - Schröder-Bergen, Susanne (Geographies of the Platform Economy. Economic Geography, 2024)
Platform-produced data play an important role in techno-capitalist platforms. Especially important in this context are open and free geospatial data, as geospatial data are becoming increasingly relevant in all aspects of daily life as well as for Web businesses. This chapter focuses on the example of the OpenStreetMap project and contrasts it with two techno-capitalist platforms: Meta/Facebook and Grab. OpenStreetMap is often considered the most successful crowdsourced geodatabase, which derives its prosperity from communities of map contributors. Conversely, companies such as Meta/Facebook and Grab are seen as part of platform capitalism, and for them to succeed, they need geospatial data. To satisfy this craving for geospatial data, these companies have chosen not to develop complete solutions or use other commercial data sources. Instead, they tap into data that OpenStreetMap provides and have started to contribute both data and software to OpenStreetMap. This chapter theoretically contextualizes the growing relevance of techno-capitalist platforms for OpenStreetMap: on the one hand, actors of platform capitalism may dominate epistemologies or exploit volunteers by using their “mapping labor” for their commercial purposes; on the other hand, techno-capitalist platforms may also provide incentives for empowering marginalized groups who can now literally put themselves on the ma

De/colonizing OpenStreetMap? Local mappers, humanitarian and commercial actors and the changing modes of collaborative mapping - Schröder-Bergen, Susanne; Glasze, Georg; Michel, Boris; Dammann, Finn (Geo Journal, 2022)
In its early days, the geodata and mapping project OpenStreetMap (OSM) was widely celebrated for opening up and “democratizing” the production of geographic knowledge. However, critical research highlights that the new socio-technical practices of collaborative mapping often also produce or reproduce patterns of exclusion, not least in the area of relative data density between the Global South and North. These findings notwithstanding, we consider it important to acknowledge the increasing number of contributions of geodata from regions outside the old European core of OSM. This expansion of geodata production in OSM is related to a diversification of OSM actors and socio-technical practices. While OSM has often been described as a crowd-based project bringing together thousands of individual craft mappers, our analysis of OSM metadata indicates new institutional actors are gaining relevance. These developments have not only resulted in new collaborations but also conflicts between local mapping communities and institutional actors. We interpret these processes in two ways. First, the expansion of mapping activities can be viewed as a decolonizing process, whereby quantitative differences in data density between the Global North and South are partly reduced and new groups of local mappers are empowered to produce geographic knowledge. Second, these new developments can also be understood as colonizing processes. The engagement of large commercial actors in OSM raises concerns that the project (and its local mappers) could be used as a new means of data extraction and that in particular new and diverse voices in the OSM community are marginalized by a fixation on economically exploitable, modernistic and universalistic epistemologies. However, this supposedly clear distinction should not obscure the fact that colonizing and decolonizing processes intertwine in complex ways.
Keywords: Critical cartography; OpenStreetMap; Volunteered geographic information; Local knowledge; Geoweb; Data extractivism; Digital commons

Digital commoning as an alternative form of social organization: The example of OpenStreetMap - Schröder-Bergen, Susanne; Glasze, Georg (2024)
Keywords: OpenStreetMap; Digital Commons; Digital Commoning; Geospatial Data Production

From Neoliberal Openness to Sovereign Openness: Analysing Imaginaries of European Digital Policies - Münßinger, Max; Schröder-Bergen, Susanne; Glasze, Georg (Geopolitics, 2025)
Numerous studies have shown that the adoption of ‘digital sovereignty’ as a guiding principle in European digital policy has marked a discursive break. While EU digital policies until the 2000s were shaped by ideas of a dismantling of borders and an opening up into a global information society, ‘sovereignty’ connotes delimitation and autonomy. Yet several recent European digital policies link ‘digital sovereignty’ also to ‘openness’. To explain this paradoxical observation, this paper adopts a cultural political economy perspective. We begin by reconstructing how the established imaginary of ‘digital openness’ has been confronted and rearticulated by demands for ‘digital sovereignty’ and then focus on two current arenas of European digital policy: the creation of a European ‘open’ cloud, and the promotion of ‘open’ digital commons. We show that ‘openness’ remains a key concept in EU digital policy, but ‘market-opening’ forms of openness have been replaced by a ‘market-protecting’ ‘sovereign openness
CRIS-Team Scopus Importer:2025-05-30

Google Maps and OpenStreetMap: The coexistence of two unequal siblings - Schröder-Bergen, Susanne (2024)
Keywords: Mapping; Google Maps; OpenStreetMap; Tech; Geospatial

The Politics of Geodata in Urban Platform Capitalism - Michel, Boris; Schröder-Bergen, Susanne (Platformization of Urban Life. Towards a Technocapitalist Transformation of European Cities, 2022)
The increasing platformization of urban life needs critical perspectives to examine changing everyday practices and power shifts brought about by the expansion of digital platforms mediating care-services, housing, and mobility. This book addresses new modes of producing urban spaces and societies. It brings both platform researchers and activists from various fields related to critical urban studies and labour activism into dialogue. The contributors engage with the socio-spatial and normative implications of platform-mediated urban everyday life and urban futures, going beyond a rigid techno-dystopian stance in order to include an understanding of platforms as sites of social creativity and exchang
CRIS-Team Scopus Importer:2022-10-28
Keywords: Openstreetmap; Plattformkapitalismus; Geodata